Advances in the superhydrophilicity-modified titanium surfaces with antibacterial and pro-osteogenesis properties: A review - Shao, Hanyu; Ma, Mingchen; Wang, Qiang; Yan, Tingting; Zhao, Baohong; Guo, Shu; Tong, Shuang (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, the rate of implant failure has been increasing. Microbial infection was the primary cause, and the main stages included bacterial adhesion, biofilm formation, and severe inhibition of implant osseointegration. Various biomaterials and their preparation methods have emerged to produce specific implants with antimicrobial or bactericidal properties to reduce implant infection caused by bacterial adhesion and effectively promote bone and implant integration. In this study, we reviewed the research progress of bone integration promotion and antibacterial action of superhydrophilic surfaces based on titanium alloys. First, the adverse reactions caused by bacterial adhesion to the implant surface, including infection and bone integration deficiency, are briefly introduced. Several commonly used antibacterial methods of titanium alloys are introduced. Secondly, we discuss the antibacterial properties of superhydrophilic surfaces based on ultraviolet photo-functionalization and plasma treatment, in contrast to the antibacterial principle of superhydrophobic surface morphology. Thirdly, the osteogenic effects of superhydrophilic surfaces are described, according to the processes of osseointegration: osteogenic immunity, angiogenesis, and osteogenic related cells. Finally, we discuss the challenges and prospects for the development of this superhydrophilic surface in clinical applications, as well as the prominent strategies and directions for future research.